A Freudian Analysis of Rosa’s Personality Structure in Film the House (Chapter Three) - Ilahi, Ruhul Justice; Prihandini, Asih (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
The paper explores the personality structure of Rosa in Chapter Three of The House, using Freud's (1923) model of id, ego, superego. The paper aims to uncover how Rosa's psychological traits manifested and how the conflict fuels her fixation behaviours and detachment from reality. Furthermore, this paper employs a qualitative descriptive method, analyzing selected scenes through repeated viewing, transcription, and thematic coding based on Freudian categories of id, ego, superego and defense mechanisms. The findings reveal that Rosa's personality is predominantly governed by the id, her ego operates defensively through rationalization, denial, repression, projection, displacement and regression. Her superego was distorted, reinforcing her morality towards property rather than empathy. These structures intensify her deterioration, resulting in a shift towards self-preservation at the end. At the end of the narrative, this shift marks a critical psychological turning point in which Rosa’s fixation on property collapses under the pressure of external reality. Her late emergence of survival instinct demonstrates the failure of her defense mechanisms to sustain the dominance of the id and the distortion of the superego. This finding highlights how unresolved fixation and imbalance among the id, ego, and superego can lead to severe psychological breakdown, particularly when an individual prioritizes material attachment over social and emotional connection. Therefore, the study emphasizes the importance of examining character psychology in film as a reflection of broader human behavioral patterns within psychoanalytic discourse.